Jahresbericht des Vereins Kunsthalle Bern 1993. - Hahnloser, Bernhard; Loock, Ulrich; Kunsthalle Bern (Bern : Kunsthalle Bern, 1994)
Brignoni, SErge ; Sauter, Dorothee ; Schropp, Leopold ; Bruly Bouabré, Frédéric ; Höfer, Candida ; Wiitasalo, Shirley ; Marden, Brice ; etc.
Duits
boek